1
$\begingroup$

I understand that you can move the $3c$ to the other side of the $=$ sign and you get $-3c$. But how can you move the $i$ so that the equation becomes $d=3ci$.

Thanks in advance

$\endgroup$
  • 1
    $\begingroup$ di=-3c. Multiply both sides by i and you get -d=-3ci. Multiply both sides by -1 to get d=3ci. Not, you just inadvertently proven 1/i = -i. Because x = 1/i means xi = 1 means xii = 1i means -x = i means x=-i. Remember that!!! It'll come in handy. Also remember $i^4=1$ So $1/i = i^{-1}=i^3=-i $. That will come in handy. A LOT $\endgroup$ – fleablood Jun 5 '16 at 22:04
1
$\begingroup$

First, as you mention, \begin{align*} di=-3c. \end{align*}

Then, we want to multiply $di$ by the inverse of $i$ (to remove $i$). The inverse of $i$ is $-i$ because $-i\times i=1$. If we multiply the left-hand side by $-i$ we also have to multiply the right-hand side by $-i$ which gives us \begin{align*} d=(-i)\times di=(-i)\times -3c=3ci, \end{align*} as desired.

$\endgroup$
  • $\begingroup$ Thanks. Your answer was clear. $\endgroup$ – Aaron Jun 5 '16 at 20:30
  • $\begingroup$ You're welcome! $\endgroup$ – Karla H. Jun 5 '16 at 20:39
2
$\begingroup$

You multiply both sides by $i$ : $di^2+3ic=3ic-d=0$. Thus $d=3ci$. To make an $i$ vanish you multiply it by $i$ because $i^2=-1$.

$\endgroup$
1
$\begingroup$

YOu have $$d = -{3c\over i}.$$ Since $i\cdot(-i) = 1$, $1/i = -i$. Now you can divide the first equation to get $$d = 3ci.$$

$\endgroup$
1
$\begingroup$

Multiply $i$ on both sides and then multipliy with $-1$ on both sides.

$\endgroup$
  • $\begingroup$ Consider that $i^2=-1$. So after multiplying with $i$ on both sides we obain $-d=-3ci$, multiplying with $-1$ gives the result you wanted. $\endgroup$ – Tesla Jun 5 '16 at 20:30
1
$\begingroup$

Others have answered but I want to point out something that will save you a lot of trouble later.

$i^1 = i $

$i^2 = -1$

$i^3 = -i $

$i^4 = -i*i=-(-1)=1$

$i*(-i)=1$ so $1/i = -i = i^3$ and $1/-i = i $

So if you ever have $xi = y $ you can always do $x= xi/i = y/i = y (-i)=-yi $.

Also if you get $5i^{27} + 3i^3 = xi + 2xi^3$

You know $i^4=1$ So $i^{27}=(i^4)^8*i^3=1^8*i^3=i^3=-i$.

So you know $-5i-3i=xi-2xi$ so $-8i = -xi $ so $x=8$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.